Health profile of school dropout children in slums of the municipal corporation area of a city - Dhande, Vishal Samadhan; Gadekar, R. D.; Doibale, M. K.; Gattani, P. L.; Domple, V. K.; Inamdar, I. F. (International Journal Of Community Medicine And Public Health, 2019)
Background: Though the school health services cater to health needs to an extent, the children who drop out of schools lose on this count. These children never derive the attention for the reason of school dropouts nor are they covered under any major health programs pertaining to their health problems. The objective of the study were to study health profile of the school dropout children aged 7–16 years residing in the slums of municipal corporation area of Nanded city; to study socio-demographic factors of the families of these school dropout children. Methods: It was a community based cross-sectional study carried out in urban slums of Municipal Corporation of the Nanded city in Maharashtra on the children of age group 7 to 16 who dropped out from the school. Total 455 study subjects were studied by using simple random sampling method. A pre-designed and pre-tested questionnaire was used to collect information on socio demographic variables. Thorough clinical examination of each subject was carried out. Results: The mean age of study subjects was 14.2 (±1.9 SD) years. Out of total 455 study subjects, 264 (58%) were boys and 191 (42%) were girls. 11.20% study subjects were having skin infections, 25.71% were having dental caries, 3.29% were having ear impairment, 9.89% were having visual impairment, and 1.31% was having stammering of speech. Conclusions: Anaemia, skin infections, dental caries, visual impairment were major health problems noted in the school dropped out children. Poor socioeconomic status, religion, type of family, more number of children in the family was some sociodemographic factors responsible for school dropout.